A case of foreign body granuloma caused by 'Bong‐chim' at the site of postherpetic neuralgia. (20th April 2020) - Seol, Jung Eun; Cho, Gyeong Je; Park, So Hee; Kim, Hyojin
Abstract: Foreign body granuloma is a potential adverse effect of acupuncture and usually occurs as an inflammatory reaction to foreign bodies that are accidentally or intentionally injected. This case presents a foreign body granuloma caused by honeybee acupuncture at the site of postherpetic neuralgia and highlights the need for caution and awareness of the side effects of acupuncture‐related procedures.